Secondary battery and electric device
By using lithium-containing transition metal oxides and phosphates as positive electrode active materials in lithium-ion secondary batteries and performing surface modification, the problem that lithium-ion secondary batteries in the prior art are difficult to have high power density and high temperature storage performance, and better battery performance is achieved.
Patent Information
- Application Number
- CN202411527026.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-04-18
AI Technical Summary
When using lithium-containing transition metal oxides as the positive electrode active material, existing lithium-ion secondary batteries are difficult to have high power density and good high-temperature storage performance.
The lithium-ion secondary battery is formed by using lithium-containing transition metal oxides and lithium-containing transition metal phosphate as the positive electrode active material and modifying it on the surface of the material to improve interface stability.
The high power density and good high-temperature storage performance of lithium-ion secondary batteries have been achieved, which significantly improves the circulation performance and storage life of the secondary batteries.
Smart Images

Figure CN119852486A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a lithium-ion secondary battery and an electrical device. Background Art
[0002] Lithium-ion batteries have gradually become the mainstream choice in the portable electronic devices, electric vehicles and hybrid vehicles markets due to their advantages such as high energy density, long cycle life and no memory effect. Among various types of positive electrode active materials, lithium-containing transition metal oxides (such as ternary positive electrode materials, such as lithium nickel cobalt manganese oxide) are widely used due to their high discharge specific capacity. However, in the prior art, when lithium-containing transition metal oxides are used as positive electrode active materials for secondary batteries, it is difficult for the secondary batteries to have both high power density and good high-temperature storage performance.
[0003] Therefore, it is necessary to provide a lithium ion secondary battery, which contains a lithium-containing transition metal oxide as a positive electrode active material and has both high power density and good high temperature storage performance. Summary of the invention
[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide a lithium-ion secondary battery and an electrical device having both high power density and good high-temperature storage performance.
[0005] The inventors have discovered that the above objectives can be achieved by adopting the technical solution of the present application.
[0006] A first aspect of the present application provides a lithium-ion secondary battery, characterized in that the secondary battery comprises a positive electrode sheet,
[0007] The positive electrode sheet comprises a positive electrode current collector and a positive electrode film layer disposed on the positive electrode current collector and comprising a positive electrode active material, wherein:
[0008] The positive electrode active material includes a lithium-containing transition metal oxide and a lithium-containing transition metal phosphate.
[0009] The lithium-containing transition metal oxide comprises nickel, cobalt, manganese and / or aluminum, and titanium. The average mass concentration of titanium in the outer region corresponding to a 1 / 4 radius extending from the surface of the primary particle of the lithium-containing transition metal oxide to the center is greater than the average mass concentration of titanium in the core region corresponding to a 1 / 4 radius extending from the center of the primary particle to the surface.
[0010] The lithium-containing transition metal phosphate includes an iron element, and the lithium-containing transition metal phosphate includes secondary particles formed by agglomeration of primary particles.
[0011] The lithium-ion secondary battery of the present application has both high power density and good high-temperature storage performance.
[0012] In any embodiment, the positive electrode sheet has an exothermic integrated peak area of 400 J / g to 1000 J / g as measured by differential scanning calorimetry (DSC).
[0013] In any embodiment, the positive electrode sheet has an exothermic integrated peak area of 400 J / g to 800 J / g as measured by differential scanning calorimetry (DSC).
[0014] In any embodiment, the average mass concentration of titanium element in the outer region extending from the surface of the primary particle of the lithium-containing transition metal oxide to the center corresponding to 1 / 4 of the radius is 0.1%-0.6%.
[0015] In any embodiment, the average mass concentration of titanium element in the core region extending from the center of the primary particle of the lithium-containing transition metal oxide to the surface corresponding to 1 / 4 of the radius is 0%-0.05%.
[0016] In any embodiment, the average particle size of the primary particles of the lithium-containing transition metal oxide is 1 μm to 5 μm.
[0017] In any embodiment, the volume average particle size Dv50 of the lithium-containing transition metal oxide is 2 μm to 10 μm.
[0018] In any embodiment, the volume average particle size Dv50 of the lithium-containing transition metal phosphate is 2 μm to 15 μm.
[0019] In any embodiment, the specific surface area of the lithium-containing transition metal phosphate is 2 m 2 / g to 10m 2 / g.
[0020] In any embodiment, the lithium-containing transition metal phosphate has the formula Li m1 Fe x Mn r P y O j1 Q1 q1 , wherein Q1 includes at least one of Al, Na, K, Mg, Cu, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, and Br, 0.6≤m1≤1.15, x>0, r≥0, 0.9≤x+r≤1, 0.95≤y≤1, 3.5≤j1≤4, and 0≤q1≤0.1.
[0021] In any embodiment, the lithium-containing transition metal oxide has a molecular formula Li m2 (Ni a Co b Mn c )1- d Ti d O j2 Q2 q2 , wherein Q2 includes one or more of Zr, Si, Nb, Al, P, Sr, W, B, Ba, Mg, Sn, Y, Na, S, N, F, Cl, Br and I, 0.6≤m2≤1.5, 0.3≤a≤0.7, 0.02≤b≤0.15, a+b+c=1, 0<d≤0.1, 1.8≤j2≤2, 0≤q2≤0.2, j2+q2=2.
[0022] In any embodiment, the mass ratio of the lithium-containing transition metal oxide to the lithium-containing transition metal phosphate is 2:1 to 50:1.
[0023] The second aspect of the present application provides an electrical device, which includes the lithium-ion secondary battery described in the first aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is a schematic diagram of a secondary battery according to one embodiment of the present application.
[0025] Figure 2 yes Figure 1 An exploded view of a secondary battery according to an embodiment of the present application is shown.
[0026] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application.
[0027] Figure 4 It is a schematic diagram of a battery pack according to one embodiment of the present application.
[0028] Figure 5 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown.
[0029] Figure 6 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.
[0030] Description of reference numerals:
[0031] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 top cover assembly DETAILED DESCRIPTION
[0032] Hereinafter, the lithium-ion secondary battery of the present application, its preparation method and the embodiment of the electric device thereof are specifically disclosed with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0033] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0034] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0035] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0036] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0037] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0038] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0039] Lithium-ion batteries have gradually become the mainstream choice in the portable electronic devices, electric vehicles and hybrid vehicles markets due to their advantages such as high energy density, long cycle life and no memory effect. Among various types of positive electrode active materials, lithium-containing transition metal oxides (such as ternary positive electrode materials, such as lithium nickel cobalt manganese oxide) are widely used due to their high discharge specific capacity. However, in the prior art, when lithium-containing transition metal oxides are used as positive electrode active materials for secondary batteries, it is difficult for secondary batteries to have both high power density and good high temperature storage performance. Therefore, it is necessary to provide a lithium-ion secondary battery, which contains lithium-containing transition metal oxides as positive electrode active materials and has both high power density and good high temperature storage performance.
[0040] Based on this, the present application proposes a technical solution to solve the above technical problems.
[0041] A first aspect of the present application provides a lithium-ion secondary battery, characterized in that the secondary battery comprises a positive electrode sheet,
[0042] The positive electrode sheet comprises a positive electrode current collector and a positive electrode film layer disposed on the positive electrode current collector and comprising a positive electrode active material, wherein:
[0043] The positive electrode active material includes a lithium-containing transition metal oxide and a lithium-containing transition metal phosphate.
[0044] The lithium-containing transition metal oxide comprises nickel, cobalt, manganese and / or aluminum, and titanium. The average mass concentration of titanium in the outer region corresponding to a 1 / 4 radius extending from the surface of the primary particle of the lithium-containing transition metal oxide to the center is greater than the average mass concentration of titanium in the core region corresponding to a 1 / 4 radius extending from the center of the primary particle to the surface.
[0045] The lithium-containing transition metal phosphate includes an iron element, and the lithium-containing transition metal phosphate includes secondary particles formed by agglomeration of primary particles.
[0046] The surface of the primary particles containing lithium transition metal oxides is the part where the positive electrode active material is in direct contact with the electrolyte. Side reactions occur and byproducts are deposited on this surface. Interface stability is crucial to improving the cycle performance and storage life of secondary batteries, especially in high voltage (~4.5V) systems. The outer area corresponding to the 1 / 4 radius extending from the surface of the primary particle to the center is the surface and near the surface of the positive electrode active material, and the side reactions are intense under high voltage; correspondingly, the core area corresponding to the 1 / 4 radius extending from the center of the primary particle to the surface is the bulk phase of the positive electrode active material, which is not easy to have side reactions with the electrolyte; therefore, controlling the coating of the modified elements on the material surface and reducing the exposed surface of the material (i.e., direct contact with the electrolyte) can directly reduce the interface side reactions and significantly improve the cycle performance and storage life of the secondary battery.
[0047] When the average mass concentration of titanium in the outer region corresponding to the 1 / 4 radius extending from the surface of the primary particle of the lithium-containing transition metal oxide to the center is greater than the average mass concentration of titanium in the core region corresponding to the 1 / 4 radius extending from the center of the primary particle to the surface, a good coating layer will be formed due to the rich titanium on the surface, which will passivate the surface of the lithium-containing transition metal oxide material, provide a good physical barrier between the electrode and the electrolyte, reduce the side reaction between the positive electrode active material and the electrolyte, and prevent the material structure from being destroyed under high voltage (~4.5V), so that the secondary battery has good high-temperature storage performance and cycle performance; when the positive electrode active material also includes a lithium-containing transition metal phosphate, and the lithium-containing transition metal phosphate includes iron, and the lithium-containing When the transition metal phosphate includes secondary particles formed by agglomeration of primary particles, due to the smaller specific surface area of the secondary particles, the particle size of the secondary particles is closer to that of the lithium-containing transition metal oxide, which is more conducive to matching large-scale industrial processing technology without deteriorating the slurry processing performance; in addition, the voltage drop rate of the lithium-containing transition metal oxide is fast at low SOC, while the lithium-containing transition metal phosphate forms a small platform at low SOC. Therefore, by adding the lithium-containing transition metal phosphate, the voltage drop in the low SOC segment becomes slower overall, unlike when pure lithium-containing transition metal oxide is used, a large voltage drop directly occurs. Therefore, it is possible to delay the voltage drop rate at low SOC, improve the kinetic performance, and thus improve the power performance of the secondary battery.
[0048] Therefore, the lithium-ion secondary battery of the present application has both high power density and good high-temperature storage performance.
[0049] The lithium-containing transition metal oxide and the lithium-containing transition metal phosphate can be distinguished by any means known to those skilled in the art, such as by SEM and / or EDS.
[0050] Whether the lithium-containing transition metal phosphate includes secondary particles formed by agglomeration of primary particles can be determined by any means known to those skilled in the art, such as by SEM.
[0051] In the present application, the lithium-containing transition metal oxide is modified by Ti, and the modification may be specifically in the form of doping and / or coating. In some embodiments, the modification is in the form of coating.
[0052] In some embodiments, the positive electrode sheet has an exothermic integrated peak area of 400 J / g to 1000 J / g as measured by differential scanning calorimetry (DSC).
[0053] In some embodiments, the positive electrode sheet has an exothermic integrated peak area of 500 J / g to 900 J / g as measured by differential scanning calorimetry (DSC).
[0054] In some embodiments, the exothermic integrated peak area of the positive electrode plate measured by differential scanning calorimetry (DSC) is 400 J / g, 450 J / g, 500 J / g, 550 J / g, 600 J / g, 650 J / g, 700 J / g, 750 J / g, 800 J / g, 850 J / g, 900 J / g, 950 J / g, 1000 J / g, or a range consisting of any two of the above values or a value within the range.
[0055] In some embodiments, the positive electrode sheet has an exothermic integrated peak area of 400 J / g to 800 J / g as measured by differential scanning calorimetry (DSC).
[0056] In some embodiments, the average mass concentration of titanium element in the outer region extending from the surface of the primary particle of the lithium-containing transition metal oxide to the center corresponding to 1 / 4 of the radius is 0.1%-0.6%.
[0057] In some embodiments, the average mass concentration of titanium element in the outer area corresponding to the 1 / 4 radius extending from the surface of the primary particle of the lithium transition metal oxide to the center is 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, or a range consisting of any two of the above values or a value in the range.
[0058] In some embodiments, the average mass concentration of titanium element in the outer region extending from the surface of the primary particle of the lithium-containing transition metal oxide to the center corresponding to 1 / 4 of the radius is 0.2%-0.4%.
[0059] In some embodiments, the average mass concentration of titanium in the core region corresponding to 1 / 4 radius from the center of the primary particle of the lithium transition metal oxide to the surface is 0%-0.05%. In some embodiments, the average mass concentration of titanium in the core region corresponding to 1 / 4 radius from the center of the primary particle of the lithium transition metal oxide to the surface is 0%-0.03%.
[0060] In some embodiments, the average mass concentration of titanium element in the core region corresponding to the 1 / 4 radius extending from the center of the primary particle of the lithium transition metal oxide to the surface is 0.05%, 0.04%, 0.03%, 0.02%, 0.01%, 0%, or a range consisting of any two of the above values or a value within the range.
[0061] In some embodiments, the average particle size of the primary particles of the lithium-containing transition metal oxide is 1 μm to 5 μm. In some embodiments, the average particle size of the primary particles of the lithium-containing transition metal oxide is 2 μm to 3 μm. In some embodiments, the average particle size of the primary particles of the lithium-containing transition metal oxide is 1 μm to 3 μm. In some embodiments, the average particle size of the primary particles of the lithium-containing transition metal oxide is 1.5 μm to 2.5 μm.
[0062] In some embodiments, the average particle size of the primary particles of the lithium transition metal oxide is 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, 2.6 μm, 2.7 μm, 2.8 μm, 2.9 μm. , 3μm, 3.1μm, 3.2μm, 3.3μm, 3.4μm, 3.5μm, 3.6μm, 3.7μm, 3.8μm, 3.9μm, 4μm, 4.1μm, 4.2μm, 4.3μm, 4.4μm, 4.5μm, 4.6μm, 4.7μm, 4.8μm, 4.9μm, 5μm, or a range consisting of any two of the above values or a value in that range.
[0063] In some embodiments, the volume average particle size Dv50 of the lithium-containing transition metal oxide is 2 μm to 10 μm. In some embodiments, the volume average particle size Dv50 of the lithium-containing transition metal oxide is 3 μm to 6 μm.
[0064] In some embodiments, the average particle size of the primary particles of the lithium transition metal phosphate is 10 nm to 1000 nm. In some embodiments, the average particle size of the primary particles of the lithium transition metal phosphate is 50 nm to 500 nm. In some embodiments, the average particle size of the primary particles of the lithium transition metal phosphate is 100 nm to 300 nm.
[0065] In some embodiments, the average particle size of the primary particles of the lithium transition metal phosphate is 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm, 800nm, 850nm, 900nm, 950nm, 1000nm, or a range consisting of any two of the above values or a value in the range.
[0066] The primary particles of lithium-containing transition metal phosphates are nanometer-sized, with a small average particle size, a short lithium ion transmission path, a fast transmission speed, and good kinetic performance. Including such lithium-containing transition metal phosphates in the positive electrode active material enables the secondary battery to have good power performance. In addition, the cost of lithium-containing transition metal phosphates is relatively low, so it can also reduce costs and is more suitable for commercial production and application.
[0067] In some embodiments, the volume average particle size Dv50 of the lithium-containing transition metal phosphate is 2 μm to 15 μm. In some embodiments, the volume average particle size Dv50 of the lithium-containing transition metal phosphate is 6 μm to 15 μm. In some embodiments, the volume average particle size Dv50 of the lithium-containing transition metal phosphate is 6.5 μm to 12 μm.
[0068] In some embodiments, the volume average particle size Dv50 of the lithium-containing transition metal phosphate is 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm, 10μm, 10.5μm, 11μm, 11.5μm, 12μm, 12.5μm, 13μm, 13.5μm, 14μm, 14.5μm, 15μm, or a range consisting of any two of the above values or a value in the range.
[0069] In some embodiments, the volume average particle size Dv50 of the lithium-containing transition metal phosphate is from 2 μm to 10 μm.
[0070] In some embodiments, the specific surface area of the lithium-containing transition metal phosphate is 2 m 2 / g to 10m 2 In some embodiments, the specific surface area of the lithium-containing transition metal phosphate is 7 m 2 / g to 9.5m 2In some embodiments, the specific surface area of the lithium-containing transition metal phosphate is 7 m 2 / g to 9m 2 / g.
[0071] In some embodiments, the specific surface area of the lithium-containing transition metal phosphate is 2 m 2 / g, 2.5m 2 / g, 3m 2 / g, 3.5m 2 / g, 4m 2 / g, 4.5m 2 / g, 5m 2 / g, 5.5m 2 / g, 6m 2 / g, 6.5m 2 / g, 7m 2 / g, 7.5m 2 / g, 8m 2 / g, 8.3m 2 / g, 8.5m 2 / g, 9m 2 / g, 9.5m 2 / g, 10m 2 / g, or a range consisting of any two of the above values or a value within the range.
[0072] In some embodiments, the lithium-containing transition metal phosphate has the formula Li m1 Fe x Mn r P y O j1 Q1 q1 , wherein Q1 includes at least one of Al, Na, K, Mg, Cu, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, and Br, 0.6≤m1≤1.15, x>0, r≥0, 0.9≤x+r≤1, 0.95≤y≤1, 3.5≤j1≤4, and 0≤q1≤0.1.
[0073] In some embodiments, the lithium-containing transition metal phosphate has the formula Li m1 Fe x Mn r P y O j1 Q1 q1, where m1 can be 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 0.98, 1.00, 1.03, 1.05, 1.08, 1.10, 1.13, 1.15, x can be 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1.0, and r can be 0, 0.05, 0. 1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, y can be 0.95, 0.96, 0.97, 0.98, 0.99, 1.00, j1 can be 3.5, 3.6, 3.7, 3.8, 3.9, 4, q1 can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1.
[0074] In some embodiments, the lithium-containing transition metal oxide has a molecular formula Li m2 (Ni a Co b Mn c ) 1- d Ti d O j2 Q2 q2 , wherein Q2 includes one or more of Zr, Si, Nb, Al, P, Sr, W, B, Ba, Mg, Sn, Y, Na, S, N, F, Cl, Br and I, 0.6≤m2≤1.5, 0.3≤a≤0.7, 0.02≤b≤0.15, a+b+c=1, 0<d≤0.1, 1.8≤j2≤2, 0≤q2≤0.2, j2+q2=2.
[0075] In some embodiments, the lithium-containing transition metal oxide has a molecular formula Li m2 (Ni a Co b Mn c ) 1- d Ti d O j2 Q2 q2 , wherein Q2 includes one or more of Zr, Si, Nb, Al, P, and F.
[0076] In some embodiments, the lithium-containing transition metal oxide has a molecular formula Li m2 (Ni a Co b Mn c ) 1- d Ti d O j2 Q2q2 , where m2 can be 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 0.98, 1.00, 1.03, 1.05, 1.08, 1.10, 1.13, 1.15, 1.18, 1.20, 1.23, 1.25, 1.28, 1.30, 1.33, 1.35, 1.38, 1.40 , 1.43, 1.45, 1.48, 1.50, a can be 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, b can be 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0 .15, d can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, j2 can be 1.8, 1.81, 1.82, 1.83, 1.84, 1.85, 1.86, 1.87, 1.88, 1.89, 1.9, 1.91, 1.92, 1.93, 1.9 4, 1.95, 1.96, 1.97, 1.98, 1.99, 2, q2 can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.2.
[0077] In some embodiments, the mass ratio of the lithium-containing transition metal oxide to the lithium-containing transition metal phosphate is 2:1 to 50:1. In some embodiments, the mass ratio of the lithium-containing transition metal oxide to the lithium-containing transition metal phosphate is 2:1 to 40:1.
[0078] In some embodiments, the mass ratio of the lithium-containing transition metal oxide to the lithium-containing transition metal phosphate is 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, 20:1, 21:1, 22:1, 23:1, 24:1, 25:1, 26:1, 27:1, 28:1, 29:1, 30:1, 31:1, 32:1, 33:1, 34:1, 35:1, 36:1 1, 27:1, 28:1, 29:1, 30:1, 31:1, 32:1, 33:1, 34:1, 35:1, 36:1, 37:1, 38:1, 39:1, 40:1, 41:1, 42:1, 43:1, 44:1, 45:1, 46:1, 47:1, 48:1, 49:1, 50:1, or a range consisting of any two of the above values, or a value within that range.
[0079] In some embodiments, the mass ratio of the lithium-containing transition metal oxide to the lithium-containing transition metal phosphate is 2:1 to 30:1.
[0080] When the mass ratio of the lithium-containing transition metal oxide to the lithium-containing transition metal phosphate is 2:1 to 30:1, the lithium-ion secondary battery of the present application has a higher power density.
[0081] The second aspect of the present application provides an electrical device, which includes the lithium-ion secondary battery described in the first aspect of the present application.
[0082] In addition, the lithium ion secondary battery and the electric device of the present application will be described below with reference to the drawings as appropriate.
[0083] In one embodiment of the present application, a secondary battery is provided.
[0084] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0085] [Positive electrode]
[0086] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.
[0087] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0088] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0089] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0090] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0091] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0092] [Negative electrode]
[0093] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0094] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0095] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0096] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0097] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0098] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0099] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0100] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0101] [Electrolytes]
[0102] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0103] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0104] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0105] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0106] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0107] [Isolation film]
[0108] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0109] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0110] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0111] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0112] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0113] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 1 The secondary battery 5 is a square structure as an example.
[0114] In some embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0115] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0116] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0117] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0118] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0119] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0120] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited to these.
[0121] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.
[0122] Figure 6 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.
[0123] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.
[0124] Example
[0125] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0126] 1. Preparation method
[0127] Example 1
[0128] (1) Preparation of positive electrode sheet:
[0129] Nickel sulfate, manganese sulfate and cobalt sulfate were added to deionized water at a molar ratio of nickel element, cobalt element and manganese element of 55:15:30 to prepare a mixed solution, 0.4 mol / L ammonia water (as a complexing agent) and 1 mol / L sodium hydroxide aqueous solution were added, the pH of the mixed solution was adjusted to 11.3, and a coprecipitation reaction was carried out at 40°C and 600 rpm for 24 hours to prepare Ni, a precursor of the ternary positive electrode material. 0.55 Co 0.15 Mn 0.3 (OH) 2 .
[0130] First, weigh the above precursor Ni according to the molar ratio of Li: (Ni + Co + Mn) = 1.06:1 0.55 Co 0.12 Mn 0.33 (OH) 2 and lithium carbonate (Li 2 CO 3 ), mechanically mix the materials using a high-speed mixer, then place them in a kiln for sintering at 900°C for 10 hours, and after cooling to room temperature, grind them mechanically using a jet mill for 5 hours to obtain an intermediate product 1. The intermediate product 1 is mixed with 2150ppm TiO 2 The mixture was placed in a high-speed mixer for mixing, and then placed in a kiln for sintering at 500°C for 7 hours to obtain the final product, a lithium-containing transition metal oxide. The average mass concentration ratio of titanium in the outer region corresponding to the radius extending from the center to 1 / 4 of the primary particle surface of the lithium-containing transition metal oxide (CONC-external) was 0.2%, and the average mass concentration ratio of titanium in the core region corresponding to the radius extending from the center to the surface of the primary particle of the lithium-containing transition metal oxide (CONC-core) was 0.015%; the average particle size of the primary particles of the lithium-containing transition metal oxide was 2μm, and the volume average particle size Dv50 was 4μm.
[0131] Iron phosphate and lithium carbonate are used as raw materials, and glucose and polyethylene glycol are added as carbon sources, and the mass of the carbon source accounts for 17% of the total mass of the raw materials. The above raw materials are mixed in a ratio of 3.85:1:1 and wet-ground with water as the solvent. The obtained slurry is spray-dried and then sintered in a roller furnace at 760°C for 24 hours. Nitrogen is introduced during the sintering process. Then the material is naturally cooled to a temperature of less than 80°C and then discharged to obtain a calcined material. The calcined material is subjected to air flow crushing, screening, demagnetization, and vacuum packaging. The frequency of the classifier of the air flow crushing is controlled to be 50-10080Hz and the frequency of the induced draft fan is controlled to be 20-5040Hz, and the volume average particle size Dv50 is 8μm and BET is 8m 2 / g of lithium-containing transition metal phosphate.
[0132] The lithium-containing transition metal oxide and the lithium-containing transition metal phosphate were mixed uniformly at a mass ratio of 90:10 to obtain a positive electrode active material. The positive electrode sheet was measured by differential scanning calorimetry DSC to have an exothermic integrated peak area of 617 J / g. The positive electrode active material, conductive carbon black SP and binder PVDF were dispersed in a solvent NMP at a mass ratio of 98:1:1 and mixed uniformly to obtain a positive electrode slurry; the positive electrode slurry was coated with a double-sided double-control coating device at a temperature of 0.24 g / 1540.25 mm 2 The positive electrode is evenly coated on the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet is obtained.
[0133] (2) Preparation of negative electrode sheet:
[0134] The negative electrode active material artificial graphite, the conductive agent conductive carbon black, the binder styrene butadiene rubber and the thickener sodium carboxymethyl cellulose were mixed in a mass ratio of 95:1:2:2, and deionized water was added to obtain the negative electrode slurry under the action of a vacuum mixer; the negative electrode slurry was stirred at 0.16g / 1540.25mm 2 Evenly coat the copper foil; after drying the copper foil at room temperature, transfer it to a 120°C oven and dry it for 1 hour, then cold press and cut it to obtain the negative electrode sheet.
[0135] (3) Isolation film:
[0136] A 13 μm thick polyethylene film was used as the separator.
[0137] (4) Electrolyte:
[0138] Ethylene carbonate, diethyl carbonate and dimethyl carbonate were mixed in a volume ratio of 1:1:1, and LiPF 6 Dissolved in the above solution to obtain an electrolyte. In the electrolyte, LiPF 6 The concentration is 1 mol / L.
[0139] (5) Preparation of batteries:
[0140] The prepared positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator placed between the positive and negative electrode sheets to isolate them, and then wound to obtain a bare cell. The bare cell is placed in an aluminum-plastic film, and a lithium-ion battery is obtained after packaging, liquid injection, formation, and capacity division.
[0141] Embodiment 2-7
[0142] The main differences between Examples 2-7 and Example 1 are shown in Table 1.
[0143] Comparative Example 1
[0144] Compared with Example 1, Comparative Example 1 mainly differs in that the positive electrode active material does not contain lithium-containing transition metal phosphate, and the exothermic integrated peak area of the positive electrode sheet measured by differential scanning calorimetry DSC is 1023 J / g.
[0145] Comparative Example 2
[0146] Compared with Example 1, Comparative Example 2 is different in that TiO is not used in the preparation process of lithium-containing transition metal oxide. 2As a result, the average mass concentration ratio of the titanium element in the outer region extending from the surface of the primary particle of the lithium transition metal oxide to the center to 1 / 4 radius (CONC-outside) and the average mass concentration ratio of the titanium element in the core region extending from the center of the primary particle to the surface to 1 / 4 radius (CONC-core) are both 0, and the heat release integrated peak area measured by differential scanning calorimetry DSC of the positive electrode is 679 J / g.
[0147] 2. Test Method
[0148] 1. The average mass concentration ratio of titanium in the outer area extending from the surface of the primary particle of lithium transition metal oxide to the center to the 1 / 4 radius
[0149] The powder samples were prepared into electron microscope samples by resin embedding and thick ion polishing, and carbon spraying was performed before testing to increase the conductivity of the material. The particles with good flatness and polishing were selected and the electron probe (EPMA) line scanning analysis was performed by drawing a line in the center of the particles, and finally the average mass concentration ratio of titanium element in the outer area corresponding to the 1 / 4 radius extending from the surface of the primary particle containing lithium transition metal oxide to the center was obtained.
[0150] 2. The average mass concentration ratio of titanium in the core area corresponding to the 1 / 4 radius extending from the center of the primary particle of lithium-containing transition metal oxide to the surface
[0151] The powder samples were prepared into electron microscope samples by resin embedding and thick ion polishing, and carbon spraying was performed before testing to increase the conductivity of the material. The particles with good flatness and polishing were selected to draw a line in the center of the particles for electron probe (EPMA) line scanning analysis, and finally the average mass concentration ratio of titanium element in the core area corresponding to the radius extending from the center of the primary particle containing lithium transition metal oxide to the surface to 1 / 4 was obtained.
[0152] 3. Average particle size of primary particles
[0153] The software "LIBMAS Lithium-ion Battery Material Microscopic Intelligent Analysis System" is used to automatically identify the primary particles by AI, draw the particle outline, and obtain the particle quantity, number, area, and maximum caliper diameter. 2,000 particles are taken and the average is calculated.
[0154] Average primary particle size = sum of all measured particle sizes (longest diameter) / sum of all measured particle numbers.
[0155] 4. Volume average particle size Dv50
[0156] Malvern MasterSizer 3000 laser particle size analyzer was used to measure the particle size according to the standard procedure: GB / T19077-2016 / ISO 13320:2009. The specific test procedure is as follows: Take an appropriate amount of the sample to be tested, and ensure that the sample concentration is 8% to 12% shading. Add 20mL of deionized water, and ultrasonicate for 5 minutes at a frequency of 53KHz and a power of 120W to ensure that the sample is completely dispersed. Then, measure the sample according to the GB / T19077-2016 / ISO 13320:2009 standard.
[0157] 5. Specific surface area
[0158] Use a specific surface and pore analyzer and refer to the standard process: GB / T19587-2017 / ISO 9277:2010 for measurement. The specific test process is as follows: Use a special sample tube to take an appropriate amount of sample, heat and vacuum for 2 hours, and weigh the total weight after cooling to room temperature, and subtract the mass of the sample tube to obtain the sample mass. Load the sample tube into the workstation, and measure the adsorption amount of gas on the solid surface under different adsorption pressures at a constant low temperature. Based on the BET multilayer adsorption theory and its formula, the sample monolayer adsorption amount is obtained, thereby calculating the specific surface area of the unit mass of the solid sample.
[0159] 6. Exothermic integrated peak area of positive electrode active material measured by differential scanning calorimetry (DSC)
[0160] In the glove box, a small disc with a diameter of 5 mm was punched out from the middle of the electrode, placed in an HP crucible, flattened, and sealed. Then, a differential scanning calorimeter was used in a nitrogen atmosphere, with a purge gas of 60 ml / min, a protective gas of 20 ml / min, a temperature rise program of 10 degrees / min, and a temperature range of 35 degrees to 460 degrees to obtain a heat flow-thermal enthalpy change diagram, thereby obtaining the exothermic integrated peak area.
[0161] 7. 10S power density
[0162] At -10℃, the battery was fully charged at 0.33C rate, left to stand for 30 minutes, and then discharged at a constant current to adjust the battery to 10% SOC state, and a certain pulse current was applied. The output voltage and current of the battery were measured, and the output power of the battery was calculated based on the voltage and current. The power density of the battery was calculated based on the battery power.
[0163] 8. High temperature storage performance
[0164] The high-temperature storage performance is characterized by the capacity retention rate after 60 days of high-temperature storage of the battery. At 25°C, the battery is charged to 4.5V at a constant current rate of 1 / 3C, and then charged at a constant voltage until the current is less than or equal to 0.05C. After standing for 30 minutes, it is discharged to 2.8V at a constant current rate of 1 / 3C. The initial discharge capacity of the battery is obtained by testing. After standing for 30 minutes, the battery is charged to 4.5V at a constant current rate of 1 / 3C, and then charged at a constant voltage until the current is less than or equal to 0.05C. The fully charged battery is then placed in a 60°C oven for storage for 60 days. The battery was taken out after 60 days of high-temperature storage, and naturally cooled to 25°C, and discharged at a constant current rate of 1 / 3C to 2.8V, then charged at a constant current rate of 1 / 3C to 4.5V, and then charged at a constant voltage to a current less than or equal to 0.05C, and then discharged at a constant current rate of 1 / 3C to 2.8V. The discharge capacity of the battery after 60 days of high-temperature storage was obtained by testing.
[0165] Capacity retention rate (%) of the battery after 60 days of high-temperature storage = discharge capacity after 60 days of high-temperature storage / initial discharge capacity×100%.
[0166] III. Analysis of test results of various embodiments and comparative examples
[0167] The lithium ion batteries of the embodiments and comparative examples were prepared according to the above method, and various parameters were measured. The relevant parameters of the positive electrode active material and the secondary battery are shown in Table 1.
[0168] Table 1: Related parameters of positive electrode active materials and secondary batteries
[0169]
[0170]
[0171] According to the above results, the secondary batteries in Examples 1-7 all include a positive electrode plate, the positive electrode plate includes a positive electrode collector and a positive electrode film layer disposed on the positive electrode collector and including a positive electrode active material, wherein the positive electrode active material includes a lithium-containing transition metal oxide and a lithium-containing transition metal phosphate, the lithium-containing transition metal oxide includes nickel, cobalt, manganese and / or aluminum, and titanium, the average mass concentration of the titanium element in the outer region corresponding to a radius extending from the surface of the primary particle of the lithium-containing transition metal oxide to the center to 1 / 4 is greater than the average mass concentration of the titanium element in the core region corresponding to a radius extending from the center of the primary particle to the surface to 1 / 4, the lithium-containing transition metal phosphate includes iron, and the lithium-containing transition metal phosphate includes secondary particles formed by agglomeration of primary particles.
[0172] From the comparison between Examples 1-7 and Comparative Examples 1-2, it can be seen that the lithium-ion secondary batteries of the embodiments of the present application have both higher power density and better high-temperature storage performance.
[0173] From the comparison between Examples 1 and 6 and Example 7, it can be seen that when the mass ratio of the lithium-containing transition metal oxide to the lithium-containing transition metal phosphate is 2:1 to 30:1, the lithium-ion secondary battery of the embodiment of the present application has a higher power density.
[0174] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A lithium ion secondary battery, characterized in that: The secondary battery comprises a positive electrode sheet, The positive electrode sheet comprises a positive electrode current collector and a positive electrode film layer disposed on the positive electrode current collector and comprising a positive electrode active material, wherein: The positive electrode active material includes a lithium-containing transition metal oxide and a lithium-containing transition metal phosphate. The lithium-containing transition metal oxide includes nickel, cobalt, manganese and / or aluminum, and titanium. The average mass concentration of titanium in the outer region corresponding to a radius of 1 / 4 extending from the surface of the primary particle of the lithium-containing transition metal oxide to the center is greater than the average mass concentration of titanium in the core region corresponding to a radius of 1 / 4 extending from the center of the primary particle to the surface. The lithium-containing transition metal phosphate includes iron. The lithium-containing transition metal phosphate includes secondary particles formed by agglomeration of primary particles.
2. The lithium ion secondary battery according to claim 1, wherein The positive electrode sheet has an exothermic integrated peak area of 400 J / g to 1000 J / g as measured by differential scanning calorimetry (DSC).
3. The lithium ion secondary battery according to claim 1 or 2, wherein: The positive electrode sheet has an exothermic integrated peak area of 400 J / g to 800 J / g as measured by differential scanning calorimetry (DSC).
4. The lithium ion secondary battery according to any one of claims 1 to 3, wherein The average mass concentration of titanium element in the outer region corresponding to 1 / 4 radius extending from the surface of the primary particle of the lithium-containing transition metal oxide to the center is 0.1%-0.6%.
5. The lithium ion secondary battery according to any one of claims 1 to 4, wherein The average mass concentration of titanium element in the core region extending from the center of the primary particle of the lithium-containing transition metal oxide to the surface to a radius corresponding to 1 / 4 is 0%-0.05%.
6. The lithium ion secondary battery according to any one of claims 1 to 5, wherein: The average particle size of the primary particles of the lithium-containing transition metal oxide is 1 μm to 5 μm.
7. The lithium ion secondary battery according to any one of claims 1 to 6, wherein: The volume average particle size Dv50 of the lithium-containing transition metal oxide is 2 μm to 10 μm.
8. The lithium ion secondary battery according to any one of claims 1 to 7, wherein: The volume average particle size Dv50 of the lithium-containing transition metal phosphate is 2 μm to 15 μm.
9. The lithium ion secondary battery according to any one of claims 1 to 8, wherein: The specific surface area of the lithium-containing transition metal phosphate is 2 m 2 / g to 10m 2 / g.
10. The lithium ion secondary battery according to any one of claims 1 to 9, wherein: The lithium-containing transition metal phosphate has a molecular formula of Li m1 Fe x Mn r P y O j1 Q1 q1 , wherein Q1 includes at least one of Al, Na, K, Mg, Cu, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, and Br, 0.6≤m1≤1.15, x>0, r≥0, 0.9≤x+r≤1, 0.95≤y≤1, 3.5≤j1≤4, and 0≤q1≤0.
1.
11. The lithium ion secondary battery according to any one of claims 1 to 10, wherein: The lithium-containing transition metal oxide has a molecular formula of Li m2 (Ni a Co b Mn c ) 1-d Ti d O j2 Q2 q2 , wherein Q2 includes one or more of Zr, Si, Nb, Al, P, Sr, W, B, Ba, Mg, Sn, Y, Na, S, N, F, Cl, Br and I, 0.6≤m2≤1.5, 0.3≤a≤0.7, 0.02≤b≤0.15, a+b+c=1, 0<d≤0.1, 1.8≤j2≤2, 0≤q2≤0.2, j2+q2=2.
12. The lithium ion secondary battery according to any one of claims 1 to 11, wherein: The mass ratio of the lithium-containing transition metal oxide to the lithium-containing transition metal phosphate is 2:1 to 50:
1.
13. An electrical device comprising the lithium ion secondary battery according to any one of claims 1 to 12.
Citation Information
Patent Citations
Secondary battery and preparation method thereof, and battery module, battery pack and device comprising secondary battery
CN114730910A
Secondary battery and preparation method thereof, and battery module, battery pack and device comprising secondary battery
CN114982002A
Mixed positive electrode material, positive electrode plate, preparation method, battery and device
CN115280551A
Positive electrode active material and preparation method thereof, positive electrode plate and lithium ion secondary battery
CN116014117A
Positive electrode material
JP2022048761A
Cited By
Battery cell, battery device, electric device, and energy storage device
CN120280457A
Battery monomer, battery device, power utilization device and energy storage device
CN122338174A